Suspicious of Acute Kidney Graft Rejection: Tacrolimus Pharmacokinetics Under Methylprednisolone Therapy - Bidu, Nadielle S.; Mattoso, Ricardo José Costa; de Oliveira Santos, Otávio A. C.; Alves, Izabel Almeida; Fernandes, Bruno José Dumêt; Couto, Ricardo David (Current Drug Research Reviews, 2024)
Background: Acute rejection remains one of the main complications in the first months after transplantation and may influence long-term outcomes. Tacrolimus has proven its usefulness in solid organ transplants and its monitoring through the application of pharmacokinetic concepts to optimize individual drug therapy. Objective: This research proposes to evaluate the tacrolimus pharmacokinetic parameters in patients suspected of acute kidney graft rejection under methylprednisolone pulse therapy. Methods: Eleven adult tacrolimus-treated renal recipients were selected from a prospective, single-arm, single-center cohort study, with suspicion of acute rejection although in use of methylprednisolone pulses therapy. They were followed up for three months posttransplantation, being tacrolimus trough serum concentrations determined using a chemiluminescent magnetic immunoassay, and pharmacokinetic parameters were estimated by using a nonlinear mixed-effects model implemented by Monolix 2020R1. A tacrolimus trough serum concentration range of 8 to 12 ng.mL-1 was considered therapeutic. Results: Six patients showed acute cellular rejection, and two of them in addition had an antibody- mediated rejection. Tacrolimus trough serum concentration was below the reference range in eight patients. Most patients showed a high tacrolimus concentration intrapatient and pharmacokinetic parameters variability. Conclusion: The obtained pharmacokinetics parameters helped in understanding the kidney recipient patients’ tacrolimus behavior, assisting in the improvement of individual drug therapy and reducing the risk of acute rejection episodes.
Keywords: immunosuppression therapy